International Law in Disaster Scenarios Applicable Rules and Principles - Zorzi Giustiniani, Flavia (Springer International Publishing, 2021)
The book identifies the main international concepts and rules that are of special relevance in disaster settings and critically analyses how they are implemented in such contexts. It shows that, although the crucial and growing importance of disaster response has resulted in a complex framework of international obligations, it is nonetheless guided by certain general principles/values. In particular, through an in-depth analysis of sovereignty, international cooperation and solidarity, and their manifestations in disaster contexts, the book assesses the concrete scope and nature of the obligations of the state affected by the disaster, and those of the international community, respectively. Considerable attention is devoted to the applicable legal framework governing disaster response in mixed situations of disaster and armed conflict, and to the main problems and operational challenges entailed by the involvement of foreign military personnel and assets in disaster response. The book's overall objective is to provide an authoritative overview of the development, core issues and challenges in international law with regard to disaster scenarios, and to serve as a valuable and comprehensive reference guide
Keywords: International Humanitarian Law, Law of Armed Conflict; Human Rights; International Relations; European Law; International humanitarian law; Human rights; International relations; Law-Europe